Work Place Learning Among Successful Professionals: A Case Study of Selected Television Producers in a Public Television Station - Ponnan, Ramachandran (2003)
The study describes the learning experiences of successful Television Producers in A Public Television Station (PTS). Specifically the study sought to determine how these professionals acquire knowledge and expertise at their workplace. Professionals are people with knowledge who offer special services for the orderly functioning of the society. TV producers are professionals in the television industry. These professionals need to continually learn to develop their expertise. How they learn, especially in the context of their ever changing busy workplace, is important to continuing professional education. The study is guided by the following research questions. 1) How do successful TV producers learn and acquire expertise at their workplace? 2) What contextual factors shape learning among successful TV producers? 3) How do personal characteristics and attributes facilitate learning among successful TV producers? Data were collected mainly through interviews using a semi structured question guide, observation and document analysis. Nine producers were selected purposively using criteria-based selection. Copies of documents such as program reports, annual reports and minutes of meetings were gathered to corroborate information provided by the respondents. The researcher was guided by the constant comparative analysis method. Three aspects of learning at the workplace emerged from the study. Successful producers acquire knowledge and expertise by, 1) The professional learning processes of formal and informal learning strategies. All respondents agreed to the importance of formal in-service training that they had to undergo when they are inducted into their profession. Benefits of such training are limited by resources, it is pertinent for producers to continuously seek learning opportunities on their own. 2) Learning through the understanding of broadcasting contexts, a distinct learning area emerging with the changing forms of broadcasting. Broadcasting contexts basically constitute the various stakeholders who occupy meaningful roles and even exert substantial influence on producers creating complex workplace procedures. 3) Learning through the development of personal characteristics and qualities imperative to learning among successful TV producers. These producers acquire the necessary attributes to learn from the workplace. Workplace learning emphasizes procedural knowledge of techniques and skills, and academic knowledge of facts and concepts. But learning has often overlooked dispositional knowledge of attitudes, values and interest that help professionals make well thought out decisions.